Unveiling the Impact of Risk on Income Smoothing of Indonesia Islamic Commercial Banks: English - Lestari, Novia; Khomsatun, Siti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
This study aims to test whether bank risk (financing/credit risk, liquidity risk and operating risk) had an impact on Income Smoothing (measured through Loan Loss Provisions) in Indonesia Islamic Commercial Banks or not. The research sample used 11 Indonesia Islamic Commercial Banks that established before 2015 and listed in Financial Services Authority (OJK) From 2015-2019. 11 Samples were taken using purposive sampling. The data used are secondary data from quarterly financial report, 220 in total. Hypothesis testing is done by using panel data regression method. Based on the analysis that have been made, the results shows that the financing/credit risk and liquidity risk had no impact on income smoothing. Operating risk had negative effect. While Total Loans as control variable affected dependent variable. For the size, as other control variable, do not affect the dependent varible. This study contributes to enrich the literature about income smoothing and bank risk, especially regarding operational risk which is less discussed than financing and liquidity risk.